1966
DOI: 10.1017/s0022172400040602
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal infection in thoracic surgery: experience in a subdivided ward

Abstract: We studied the incidence of staphylococcal infection in a thoracic surgery ward which consisted of a number of separate rooms, and inquired whether the subdivision of the ward was responsible for the unusually low sepsis-rate.The airborne dissemination of Staphylococcus aureus from one room to another appeared to be little less than that in an open ward; but the total number of Staph. aureus in the air was very low.Most of the patients received prophylactic antibiotics. The nasal carrier-rate of Staph. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 7 publications
(13 reference statements)
2
22
0
Order By: Relevance
“…Our own results, here and in previous work (Shooter et at. 1958; (Lidwell et al 1966), have shown a low acquisition rate similar to ours. In both wards there was a fairly high usage of antibiotics, but, presumably because the subdivision has reduced the rate of transfer of the staphylococci in some way, this has not had the effect of increasing the carrier rate in the way that it did in the patients nursed in open wards (Noble et al 1964).…”
Section: Airborne Staphylococcisupporting
confidence: 85%
See 1 more Smart Citation
“…Our own results, here and in previous work (Shooter et at. 1958; (Lidwell et al 1966), have shown a low acquisition rate similar to ours. In both wards there was a fairly high usage of antibiotics, but, presumably because the subdivision has reduced the rate of transfer of the staphylococci in some way, this has not had the effect of increasing the carrier rate in the way that it did in the patients nursed in open wards (Noble et al 1964).…”
Section: Airborne Staphylococcisupporting
confidence: 85%
“…Acquisition of the nasal carrier state The rate of acquisition of S. aureus in the nose during hospital stay has frequently been documented and has been suggested as one index of the efficiency with which a hospital layout can protect patients from cross-infection (Parker, John, Emond & Machacek, 1965;Williams, 1966;Lidwell et al 1966). In our ward 6-2 % of I4-2 213 R. E. 0.…”
Section: Broadcasts Of Staphylococcimentioning
confidence: 99%
“…A strain appearing which had not been found in previous swabs or which was different in resistance or phage-type from that found previously was assumed to have been 'acquired'. The conventions adopted for times of acquisition between swabbings were those of Lidwell et al (1966). The survey took place between November 1967 and April 1969.…”
Section: Bacteriological Examinationsmentioning
confidence: 99%
“…The enumeration of Staphylococcus aureus in the air of hospital wards may be of some value for routine monitoring in hospital hygiene (Alder & Gillespie, 1964) and also in the exploration of the hygienic consequences of particular sorts of hospital design or practice (Lidwell et al 1966;Williams, 1967). A truly selective medium for collection of S. aureus from the air would be a great advantage for either of these uses, but none of the selective media devised in the past has been found suitable.…”
Section: Commentmentioning
confidence: 99%